Analisis Penerapan Sistem Manajemen Keselamatan Kerja Di Proyek Gedung - Yuliana, Ni Putu Indah; Dewi, I Gusti Ayu Wulan Krisna; Putra, I Gusti Putu Adi Suartika; Yuni, Ni Kadek Sri Ebtha; Wahyudi, I Gede Bambang (Fakultas Teknik, Universitas Wiraraja, 2025)
The increasing development of construction projects has led to an increase of work accidents and insurance claims. This must be followed up with the implementation of a construction safety management system. This action is expected to reduce the number of accidents and illnesses due to work. The purpose of the study is to analyze the value level of implementation of construction safety management system and the factor that causing the discrepancy between the requirements and the implementation. This study uses a qualitative research method with a descriptive format. The results showed that the implementation rate of the Construction Safety Management System was 88.37% with the category of